Preparation of chitosan/mesoporous silica nanoparticle composite hydrogels for sustained co-delivery of biomacromolecules and small chemical drugs - Min Zhu, Yufang Zhu, Lingxia Zhang and Jianlin Shi (Science and Technology of Advanced Materials, 2013)
We have developed composite hydrogels of chitosan (CS) and mesoporous silica nanoparticles (MSNs) in this study. The gelation rate, gel strength, drug delivery behavior and chondrocyte proliferation properties were investigated. The introduction of MSNs into CS accelerated the gelation process at body temperature and also increased the elastic modulus G' from 1000 to 1800 Pa. When we used gentamicin (GS) and bovine serum albumin (BSA) as model small chemical drugs and biomacromolecules, respectively, the CS/MSN hydrogels released GS and BSA in a sustained manner simultaneously, but the CS hydrogels only showed sustained BSA release. Furthermore, in vitro chondrocyte culture showed that the CS/MSN composite hydrogels indeed performed much better in supporting chondrocyte growth and maintaining chondrocytic phenotype compared to the CS hydrogels. Therefore, the results suggest that the CS/MSN composite hydrogels can be potentially very useful for cartilage regeneration.